Disease-Induced Cooperation Mitigates Populations Against Decline: The Cascade Effect of Cooperation Evolution - Zhang, Feng; Cao, Menglan; Shi, Lei; Wang, Ruiwu (Frontiers in Ecology and Evolution, 2022)
Due to density-dependent selection, the ecological factors impacting population dynamics can play an important role in promoting cooperation, and accordingly, benefit a population from the eco-evolutionary feedback. This implies that cooperation between individuals could help resist the attack of infectious diseases. Yet, little is known about how cooperation evolves in response to infections. We here examined theoretically the impact of disease infections with various transmission types on cooperation evolution and its feedback to population dynamics. Results show that infected populations can evolve to be more cooperative, and the level of cooperation increases with the transmission rate, which can protect the population against decline due to infection and prevent population extinction driven by defection. A high transmission rate can stabilize population fluctuation, while a relatively low transmission rate could destabilize population dynamics. We argue that the mechanism underlying such stress-induced cooperation is analogous to the cascade effect of trophic interactions in food webs: reduction in selfishness from environmental stress indirectly relaxes the exploitation of cooperators by defectors. These findings emphasize the role of eco-evolutionary feedback in evolving cooperation and the ecological significance of cooperation evolution for populations withstanding disease infection.